What is Client Satisfaction a Mediating Variable between Promotion, Quality of Service, and Client Trust in the Decision to Use Tax Consultant Services - Sanusi, Revilia; Humairoh, Humairoh (Dinasti International Journal of Economics, Finance & Accounting, 2026)
This study aims to analyze the influence of promotion, service quality, and client trust on the decision to use the services of a tax consultant, with client satisfaction as a mediating variable in the Tax Novena in Tangerang City. This study uses a quantitative method with data collection techniques through the distribution of questionnaires to Novena Tax clients. The data analysis technique used is Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) with the help of the SmartPLS application. The results of the study show that promotion and client trust have a positive and significant effect on client satisfaction, but the quality of service does not affect client satisfaction. In addition, promotion, service quality, and client trust have a positive and significant effect on the decision to use the services of a tax consultant, while satisfaction has a significant negative effect.  The results of the indirect effect test showed that client satisfaction was not able to mediate the influence of promotion, service quality, and client trust on the decision to use the services of a tax consultant at the Tax Novena in Tangerang City. Based on the results of the study, Novena Pajak is advised to improve its promotional strategy by maintaining service quality and client trust in order to improve decisions to use tax consultant services.